Studies on fungal and bacterial population of air-conditioned environments - Ross,Claudia (2004)
In tropical countries such as Brazil, there is not enough information about microbial contaminants in indoor environments with air conditioning systems. Microbial monitoring of such environments is important for the quality of human life. The aim of this work was to assess the fungal genera and bacterial morphotypes occurring in such environments. Air samples were taken indoors and outdoors from a public auditorium, a hospital, a company and a shopping center during the 2001 winter by using a six-stage impactor Millipore M air T® . Twenty-one fungal genera were identified. Bacterial morphological groups found were Gram positive and negative rods and Gram positive coccus.